It's not about regulation... - Jan Toporowski (Danish Institute for International Studies (DIIS), 2009)
The present discussions about the future of bank regulation, coming after a long period of bank deregulation, have a natural tendency to exaggerate the effectiveness of regulation. But those discussions are poorly rooted in the macroeconomic foundations of bank intermediation, including its function of risk-bearing. The debate on financial regulation, abstracted from actual in-termediation, would be more effective as part of a more general discussion of financial reconstruction.
Keywords: 330; Bankenpolitik; Bankensystem; Bankenaufsicht; Finanzintermediär; Bankrisiko; Bankenreform; Welt